E-165 Endovascular treatment of acute ischemic stroke in octogenarians and nonagenarians compared with younger patients. (22nd July 2018) - Kawabata, Y; Nakajima, N; Fukuda, S; Tsukahara, T; Ohtani, R; Miyake, H
Abstract : Background: Endovascular therapy (EVT) for emergent large vessel occlusion has been established as the standard therapy in acute ischemic stroke. However, the effectiveness and safety in the very elderly population have not been proved. Objective: To determine the safety and effectiveness of EVT in octogenarians and nonagenarians. Methods: We retrospectively reviewed all patients who underwent EVT at two stroke centers between April 2012 and January 2018. Functional outcome was assessed using mRS at 90 day or at discharge, and compared between younger patients (age 46–79; n=38) and octogenarians and nonagenarians (age 80–93; n=17). Results: Patients aged 79 years more frequently had poor pre-stroke functional deficit (mRS >2) than younger patients (58.8% vs 7.9%, p value=0.0001). No difference was observed between very elderly and younger patients in the rate of successful recanalization of TICI 2b or 3 (88.2% vs 65.8%, p value=0.11), favorable functional outcome of mRS 0–2 (29.4% vs 44.7%, p value=0.38), and mortality (23.5% vs 26.3%, p value=0.56). Complete recanalization was observed more frequently in very elderly patients than younger patients (58.8% vs 26.3%, p value=0.03). Five of seven very elderly patients (71.4%) with pre-stroke mRS 0–2 had independent functional outcomes, and 3 of 8 patients (37.5%) with pre-stroke mRS had no mRS change after stroke. Conclusions: Our data suggest that EVT should not be withheld for large vessel occlusion in octogenarians and nonagenarians in acute ischemic stroke, especially if they have a good pre-stroke functional status. Disclosures: Y. Kawabata: None. N. Nakajima: None. S. Fukuda: None. T. Tsukahara: None. R. Ohtani: None. H. Miyake: None.